The Empowering Forest Communities through the Application of the Sonokeling Tree Barcoding System as an Effort for Forestry Social Disaster Management in Wan Abdul Rahman Forest Park, Lampung Province - Octaviani, Eti Artiningsih; Hasibuan, Mhd Muhajir; maulana, sena; sari, nurika arum; Murda, Rio Ardiansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2023)
Abstract Community Service entitled